Long Peritoneal Dialysis Dwells With Icodextrin: Kinetics of Transperitoneal Fluid and Polyglucose Transport - Olszowska, Anna; Waniewski, Jacek; Stachowska-Pietka, Joanna; Garcia-Lopez, Elvia; Lindholm, Bengt; Wańkowicz, Zofia (Frontiers in Physiology, 2019)
Background and objective: During peritoneal dialysis (PD), the period of effective net peritoneal ultrafiltration during long dwells can be extended by using the colloidal osmotic agent icodextrin but there are few detailed studies on ultrafiltration with icodextrin solution exceeding 12 h. We analyzed kinetics of peritoneal ultrafiltration in relation to icodextrin and its metabolites for 16-h dwells with icodextrin. Design, setting, participants, and measurements: In 20 clinically stable patients (mean age 54 years; 8 women; mean preceding time on PD 26 months), intraperitoneal dialysate volume (VD) was estimated from dilution of 125I-human serum albumin during 16-h dwell studies with icodextrin 7.5% solution. Sodium was measured in dialysate and plasma. In 11 patients, fractional absorption of icodextrin from dialysate, dialysate, and plasma amylase and high and low (Mw <2 kDa) Mw icodextrin fractions were analyzed. Results: Average VD increased linearly with no difference between transport types. At 16 h, the cumulative net ultrafiltration was 729 ± 337 ml (range −18 to 1,360 ml) and negative in only one patient. Average transcapillary ultrafiltration rate was 1.40 ± 0.36 ml/min, and peritoneal fluid absorption rate was 0.68 ± 0.38 ml/min. During 16 h, 41% of the initial mass of icodextrin was absorbed. Plasma sodium decreased from 138.7 ± 2.4 to 136.5 ± 3.0 mmol/L (p < 0.05). Dialysate glucose G2–G7 oligomers increased due to increase of G2–G4 metabolites while G6–G7 metabolites and higher Mw icodextrin fractions decreased. In plasma maltose and maltotriose (G2–G3 metabolites) increased while higher Mw icodextrin oligomers were almost undetectable. Dialysate amylase increased while plasma amylase decreased. Conclusions: Icodextrin resulted in linear increase of VD with sustained net UF lasting 16 h and with no significant difference between peritoneal transport types. In plasma, sodium and amylase declined, G2–G3 increased whereas larger icodextrin fractions were not detectable. In dialysate, icodextrin mass declined due to decrease of high Mw icodextrin fractions while low Mw metabolites, especially G2–G3, increased. The ability of icodextrin to provide sustained UF during very long dwells – which is usually not possible with glucose-based solutions – is especially important in anuric patients and in patients with fast peritoneal transport.